2020
DOI: 10.18805/ijare.a-5548
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bacterial Isolates against Causal Agent of Late Blight of Potato, Phytophthora infestans

Abstract: Background: Potato (Solanum tuberosum) is main crop in subtropical and temperate regions as vegetable crop. It is affected by Phytophthora infestans causing a devasting disease late blight. The chemical pesticides used against this disease in this present scenario cause pollution (soil as well as water) and adversely affect beneficial soil micro-flora, grazing animals and human beings. Methods: An experiment was designed at the Department of Botany, K.V. Subharti College of Science, Swami Vivekanand Subharti U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
1
Order By: Relevance
“…cepae, F. proliferatum, F. verticillioides and F. acuminatum, isolated from infected garlic cloves (Bjelić et al, 2018). Similarly, Rani et al (2021) observed that Bacillus showed Effect of Plant Growth Promoting Bacillus spp. on Germination and Seedling Growth of Soybean maximum zone of inhibition to the tested pathogen among the three antagonistic biocontrol agents.…”
Section: Resultsmentioning
confidence: 90%
“…cepae, F. proliferatum, F. verticillioides and F. acuminatum, isolated from infected garlic cloves (Bjelić et al, 2018). Similarly, Rani et al (2021) observed that Bacillus showed Effect of Plant Growth Promoting Bacillus spp. on Germination and Seedling Growth of Soybean maximum zone of inhibition to the tested pathogen among the three antagonistic biocontrol agents.…”
Section: Resultsmentioning
confidence: 90%
“…Dünya çapında tarımsal ürün yetiştiriciliğinde, toprak kaynaklı bitki patojenlerinin üretimde ve verimde ciddi kayıplara neden olması yüksek ürün maliyetlerine yol açmaktadır (Panth et al, 2020). Rizosferdeki mikrobiyal aktivite ise hem doğal hem de yönetilen tarımsal topraklarda patojenlerin girişine çok yatkın olan köklerde hastalığa neden olan toprak kaynaklı bitki patojenlerini baskılanmasında kilit rol oynamaktadır (Hariprasad & Umesha, 2007;Rani et al, 2007). Bu kapsamda domates bitkisinde hastalığa neden olan toprak kökenli funguslara karşı, domates bitkilerin rizosferinden izole edilen rizobakterilerin biyokontrol aktivitelerinin belirlenmesi bu çalışmada amaçlanmıştır.…”
Section: Introductionunclassified
“…Whereas literature has amply documented the biocontrol of late blight of potato using plant or bacterial extracts (Quintanilla et al, 2002;Stephan et al, 2005;Olanya and Larkin, 2006;Dorn et al, 2007;Wang et al, 2007;Hultberg et al, 2010;Moushib et al, 2013;Bengtsson et al, 2015;Hunziker et al, 2015;Rogozhin et al, 2020;Rani et al, 2021), fewer studies have reported biocontrol of potato late blight and control of the pathogen growth with metabolites extracted from fungi. For instance, the application of oosporein, an antifungal metabolite isolated from Verticillium psalliotae, fusaric acid from F. oxysporum, and culture extracts from Trichoderma and Chaetomium species (i.e., C. cochliodes and C. aureum) have been reported to affect the growth of P. infestans in vitro (Nagaoka et al, 2004;Son et al, 2008;Bae et al, 2016;Linkies et al, 2021).…”
Section: Introductionmentioning
confidence: 99%